1991
DOI: 10.1128/iai.59.3.758-763.1991
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytochalasin D and methylamine on intracellular growth of Legionella pneumophila in amoebae and human monocyte-like cells

Abstract: A cloned and axenically cultured strain of Hartmannella vermiformis was used as a model to study intracellular multiplication of Legionella pneumophila in amoebae. The growth of L. pneumophila in both H. vermiformis and a human monocyte-like cell line (U937) was investigated with cytoskeletal and metabolic inhibitors. L. pneumophila replicated only intracellularly in these cellular models, and electron microscopy showed ultrastructural similarities in the initial phases of multiplication. Treatment of amoebae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
3
5

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 39 publications
(47 reference statements)
5
71
3
5
Order By: Relevance
“…In contrast to previously published results obtained with Acanthamoeba polyphaga [33] data reported recently suggest the requirement for host protein synthesis during bacterial uptake by A. castellanii [34]. This reduction in uptake was enhanced by simultaneous addition of cytochalasin D. These ¢ndings con¢rm the proposed heterogeneity of uptake mechanisms by di¡erent protozoan hosts [27,35,36]. Apparently A. cas-tellanii uses multiple mechanisms for bacterial uptake, while H. vermiformis may use only receptor-mediated pinocytosis.…”
Section: Legionella^protozoa Interactionscontrasting
confidence: 85%
“…In contrast to previously published results obtained with Acanthamoeba polyphaga [33] data reported recently suggest the requirement for host protein synthesis during bacterial uptake by A. castellanii [34]. This reduction in uptake was enhanced by simultaneous addition of cytochalasin D. These ¢ndings con¢rm the proposed heterogeneity of uptake mechanisms by di¡erent protozoan hosts [27,35,36]. Apparently A. cas-tellanii uses multiple mechanisms for bacterial uptake, while H. vermiformis may use only receptor-mediated pinocytosis.…”
Section: Legionella^protozoa Interactionscontrasting
confidence: 85%
“…Although it has been suggested that entry of L. pneumophila into amoebae may not require actin filaments (King et al ., 1991;Moffat and Tompkins, 1992), we found that pathogen uptake is an actin-mediated process in Dictyostelium . Treatment of amoebae with a concentration of latrunculin-A sufficient to induce global depolymerization of actin filaments (Gerisch et al ., 2004) reversibly blocked detectable entry of bacteria into the cells.…”
Section: Uptake Of L Pneumophila Is Mediated By Actinmentioning
confidence: 99%
“…Many approaches have demonstrated that actin filaments play an essential role in the uptake of L. pneumophila by mammalian cells. An early study showed that cytochalasin D, an inhibitor of actin filament formation, blocked L. pneumophila replication in the monocyte-like cell line U937 (King et al, 1991). However, there has been uncertainty about the role of actin in the uptake of L. pneumophila by protozoa and amoebae, because higher concentrations of cytochalasin D than those inhibitory for monocytes failed to block growth of L. pneumophila in H. veriformis (King et al, 1991) or A. castellani (Moffat and Tompkins, 1992;Kohler et al, 2000).…”
Section: Cytoskeletal Interactions Of Early L Pneumophilacontaining mentioning
confidence: 99%
See 1 more Smart Citation
“…Yamamoto et al (36) and Husmann and Johnson (18) used cytochalasin D in order to block the phagocytosis of L. pneumophila by murine and guinea pig macrophages, respectively. It has also been shown that cytochalasin D inhibited intracellular multiplication of L. pneumophila in the U937 monocyte model, but had no effect on the intracellular multiplication of legionellas in the axenic amoeba Hartmannella vermiformis (20). Moreover the same authors described the inhibition of L. pneumophila multiplication in both U937 monocytes and H. vermiformis by methylamine, a metabolic inhibitor which affects pinocytosis acting on transglutaminase.…”
mentioning
confidence: 95%